Love, Liberation, and Escaping Slavery : William and Ellen Craft in Cultural Memory. - McCaskill, Barbara (Sarah Mills Hodge Fund Publication., 2015)
The spectacular 1848 escape of William and Ellen Craft (1824-1900; 1826-1891) from slavery in Macon, Georgia, is a dramatic story in the annals of American history. Ellen, who could pass for white, disguised herself as a gentleman slaveholder; William accompanied her as his "master's" devoted slave valet; both traveled openly by train, steamship, and carriage to arrive in free Philadelphia on Christmas Day. In Love, Liberation, and Escaping Slavery, Barbara McCaskill revisits this dual escape and examines the collaborations and partnerships that characterized the Crafts' activism for the next.